Modelling of Air Springs (Current Problems in Rail Vehicles, 2021)
The article deals with the issue of modelling air springs for use in multibody simulations. The reliability of the results of simulations fully depends on the correct parameter settings in simulation models. To set simulation models of air springs it is necessary to take into account mainly the parameters that determine their dynamic behaviour. In order to measure the dynamic properties of air springs, a test bench was designed and built in VÚKV. The introduction and the description of the test bench are parts of this article. The end of the article deals with the implementation of measured data into the simulation model of air spring and its validation.
Keywords: air spring; multibody simulation; simulation model; rail vehicles; dynamic characteristics; vertical direction; test bench; additional air reservoir; orifice; surge pipe; measurement